2020
DOI: 10.3390/biomedicines9010010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nanoparticle Penetration in the Tumor Spheroid Using Two-Photon Microscopy

Abstract: Mesoporous silica nanoparticles (MSNs) have emerged as a prominent nanomedicine platform, especially for tumor-related nanocarrier systems. However, there is increasing concern about the ability of nanoparticles (NPs) to penetrate solid tumors, resulting in compromised antitumor efficacy. Because the physicochemical properties of NPs play a significant role in their penetration and accumulation in solid tumors, it is essential to systematically study their relationship in a model system. Here, we report a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Overall, these findings suggest that NP transport is diminished relative to that observed in less complex spheroid models [92][93][94], signifying the relevance in evaluating NPs in multicellular complex environments. While this information highlights the obvious challenges in achieving NP transport, vehicle evaluation in a more complex tumor model may identify stages in which different particle types may be evaluated and potentially improved to more conservatively and realistically estimate delivery to tumor sites.…”
Section: Discussionmentioning
confidence: 79%
“…Overall, these findings suggest that NP transport is diminished relative to that observed in less complex spheroid models [92][93][94], signifying the relevance in evaluating NPs in multicellular complex environments. While this information highlights the obvious challenges in achieving NP transport, vehicle evaluation in a more complex tumor model may identify stages in which different particle types may be evaluated and potentially improved to more conservatively and realistically estimate delivery to tumor sites.…”
Section: Discussionmentioning
confidence: 79%
“…This observation was in line with the previous literature studies, wherein larger particles are known to exhibit poor permeation within tumors [ 18 ]. Pratiwi and coworkers evaluated the tumor penetration of mesoporous silica nanoparticles with sizes 25, 50, and 200 nm using two-photon excitation microscopy (TPEF) [ 15 ]. Among the nine different parameters compared, they found both the shape and size of the particles were crucial in determining the penetration characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…In another study using polymeric micelles of sizes 30, 50, 70, and 100 nm, Cabral and coworkers showed that 30 nm particles had better deep tumor penetration capability than others [ 17 ]. Previous studies have shown that smaller-sized particles are more efficient in passing through intercellular space with effective spatial distribution within the tumor spheroids [ 13 , 15 , 60 , 61 ]. Even in our studies, G X nanoparticles showed better penetration than G CC .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, confocal microscopy of the tumor spheroids after incubation with IPO demonstrated distribution of the nanoparticles throughout tumor spheroids. Our success in distributing IPO uniformly throughout the spheroids may be due to the phosphonate modification of our nanoparticles, as mesoporous silica-based nanoparticles with negative or positive charge were recently shown to penetrate into the core of tumor spheroids 38 . These nanomaterials have additional advantage to localize to perinuclear regions upon cellular uptake.…”
Section: Discussionmentioning
confidence: 99%